Temporal and spatial dynamics in emission of water-soluble ions in fine particulate matter during forest fires in Southwest China - Zhan, Xiaoyu; Ma, Yuanfan; Huang, Ziyan; Zheng, Chenyue; Lin, Haichuan; Tigabu, Mulualem; Guo, Futao (Frontiers in Forests and Global Change, 2023)
The aim of this study was to analyze changes in emission of water-soluble ions in fine particulate matter over time and in different southwest forest areas in China based on China’s Forestry Statistical Yearbook and MODIS satellite fire point data. The total amount of forest biomass combusted in southwest forest areas was 64.43 kt. Among the different forest types, the proportion of burnt subtropical evergreen broad-leaved forest was the largest (60.49%) followed by subtropical mixed coniferous and broad-leaved forest (22.78%) and subtropical evergreen coniferous forest (16.72%). During the study period, 61.19 t of water-soluble ions were released in PM2.5 from forest fires, and the emissions of Li+, Na+, NH4+, K+, Mg2+, Ca2+, F-, Cl-, Br-, NO3-, PO43- and SO42- were 0.48 t, 11.54 t, 2.51 t, 19.44 t, 2.12 t, 2.92 t, 1.94 t, 12.70 t, 1.12 t, 1.18 t, 1.17 t and 4.07 t, respectively. Yunnan was the province with the highest emissions of water-soluble ions in PM2.5 in the southwest forest areas, and the concentration K+ was the highest. Emission of water-soluble ions in Yunnan and Sichuan all showed a significant downward trend, while the overall decrease in Tibet, Chongqing and Guizhou was not significant. The peak emission of water-soluble ions in PM2.5 during forest fires appeared in spring and winter, which accounted for 87.66% of the total emission. This study reveals the spatiotemporal changes in water-soluble ion emissions from forest fires, by studying the spatiotemporal dynamics of water-soluble ions in PM2.5, we can better understand the sources, distribution, and change patterns of these ions, as well as their impact on the atmospheric environment, ecosystems, and climate change. This information is crucial for predicting and managing air pollution, as well as developing effective forest management and environmental protection policies to respond to fires; and hence concerted fire prevention efforts should be made in each province, taking into account the season with higher probability of fire occurrence to reduce the potential impact of fire-related pollutions.